The Relationship Between Mathematical Critical Thinking Ability and Students’ Political Literacy in Senior High School - Sulaiman; Wahyu Widada; Nurul Astuty Yensy; Ari Suningsih (The Indonesian Institute of Science and Technology Research, 2026)
Critical thinking and political literacy are essential competencies in 21st-century education; however, they are often developed separately in school learning. This study investigates the relationship between mathematical critical thinking ability and students’ political literacy at the senior high school level. Using a quantitative correlational design, data were collected from 80 eleventh-grade students selected through stratified random sampling from three public high schools in Yogyakarta City. The instruments consisted of a mathematical critical thinking test and a political literacy questionnaire, both of which demonstrated acceptable validity and reliability. Data were analyzed using the Pearson Product–Moment correlation. The results revealed a significant positive correlation between mathematical critical thinking and political literacy (r = 0.58, p < 0.01), indicating that students with stronger mathematical reasoning tend to exhibit higher political literacy, including a better understanding of democratic values and more rational civic attitudes. These findings demonstrate that mathematical critical thinking contributes meaningfully to students’ political literacy. The study highlights the importance of integrating socio-political contexts into mathematics instruction as an interdisciplinary approach to fostering analytical and responsible citizenship in a democratic society.